Symptom and Quality of Life Improvement in LUX-Lung 6. Issue 6 (June 2015) - Geater, Sarayut L; Xu, Chong-Rui; Zhou, Caicun; Hu, Cheng-Ping; Feng, Jifeng; Lu, Shun; Huang, Yunchao; Li, Wei; Hou, Mei; Shi, Jian Hua; Lee, Kye Young; Palmer, Michael; et al.
<x xml:space="preserve">Abstract</x> Introduction: In the phase III, LUX-Lung 6 trial, afatinib prolonged progression-free survival (PFS) versus cisplatin/gemcitabine in Asian patients with epidermal growth factor receptor (EGFR) mutation-positive non–small-cell lung cancer (NSCLC). This article provides detailed assessments of patient-reported outcomes (PROs), a LUX-Lung 6 secondary end point, and explores the relationship between PFS and health-related quality of life (QoL) in these patients. Methods: Patients (n = 364) were randomized (2:1) to oral afatinib (40 mg/day) or up to six cycles of cisplatin/gemcitabine (21-day cycle; cisplatin 75 mg/m2 [d1]; gemcitabine 1000 mg/m2 [d1, 8]). QoL was assessed using the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire and its lung cancer-specific module. The relationship between PFS (investigator assessment and independent review) and QoL was evaluated using analysis of covariance and a longitudinal model. Results: More patients treated with afatinib versus cisplatin/gemcitabine showed improvements in global health status/QoL (p < 0.0001) and physical (p < 0.0001), role (p = 0.013), and social (p < 0.001) functioning scales. Delayed symptom deterioration and better QoL over time was also observed with afatinib. QoL measured before tumor assessment was considerably poorer for patients with progression than those without progression, with significant differences in mean scores at multiple assessment time points. Results from the longitudinal analysis consistently demonstrated a significant negative impact of progression on QoL (p < 0.0001). Conclusion: Afatinib improved PFS and PROs versus chemotherapy in EGFR mutation-positive NSCLC patients. Progression was associated with statistically significant worsening in QoL measured before tumor assessment, underscoring the value of PFS as a clinically relevant end point.